Conceptualising strategic litigation - Kris van der Pas (Oñati Socio-Legal Series)
This article conceptualises the term “strategic litigation” in order to provide for a definition of it. Strategic litigation is a tool increasingly used in Europe by individuals and organisations to attain different objectives. Next to that, there is increasing academic attention for the topic. Nevertheless, the exact definition of “strategic litigation” remains unclear. Therefore, this article uses the research method of conceptualisation as well as a database research and additional literature to provide for a definition. It looks firstly at the background concept, involving the range of meanings associated with the term “strategic litigation”, after which a systematised concept is formed. Thereby, use is made of the “necessary and sufficient conditions” (NSC) approach, to develop the conditions necessary and/or sufficient for a case to fit within the category of strategic litigation. Moreover, the external conceptual relations of the term are explored.